Research on the conductivity of circuit on fabrics based on inkjet printing and electroless deposition technology. Issue 5 (January 2021) - Guo, Hua; He, Yongyan; Yue, Wangfeng; Guo, Xinyu
Abstract: Traditional silicon semiconductor substrate based electronic manufacturing has the shortcomings of non-bending, poor biocompatibility, and high cost. Fabric is more suitable for wearable electronic substrate due to its advantages of flexibility, air permeability, and skin-friendliness. We studied the manufacture of the conductive circuit based on inkjet printing and electroless deposition technology and got excellent conductivity and high dimensional accuracy circuit on fabric substrates. Three kinds of commonly used fabric materials cotton, polyester/cotton and polyester are selected to study the key work of surface pre-treatment, inkjet printing circuit pattern, and electroless deposition. The synergetic effect of SU-8 and P4VP (poly-4-vinylpyridine) on fabric ensures that the pattern retains its original size rather than diffusing. The distance between adjacent electric lines is no less than 0.3mm. With the extension of copper deposition time, the copper deposition layer becomes more and more uniform and dense. Sheet resistance reached 0.01Ω after 2 hours of copper deposition. The performance of all three kinds of fabric is similar. And cotton fabric had the best water lock performance. This technology has great potential for promotion and development in the application of intelligent textiles in the future.